Challenges of virtual classroom during COVID-19 pandemic: An empirical analysis of Indian higher education - Ajay Kumar Singh; Mukesh Kumar Meena (International Journal of Evaluation and Research in Education (IJERE), 2022)
Higher education institutions (HEIs) usually work open throughout the academic session. In the COVID-19 pandemic time, all the HEIs were also closed temporarily. The study examined the major challenges faced by the teachers and students from the virtual classroom during the nationwide lockdown. Due to the nationwide lockdown and lack of funding, convenience sampling and snowball sampling techniques were used for data collection. A total of 893 responses were analyzed for this study. Data was collected through a structured questionnaire on a Likert scale from 305 teachers and 588 students of higher education institutes from the entire India. Network connectivity was the major challenge faced by the faculty members (mean value of 3.68) followed by 3.17 mean value for lack of professional environment at home, 3.03 for lack of teaching material at home, 2.92 for lack of personal computer/laptop. Lack of professional environment at home (mean value of 3.59) was the major challenge faced by the students followed by 3.57 for lack of teaching material at home, 3.35 for network connectivity, 3.31 for lack of personal computer/laptop. Virtual classrooms have challenges such as poor internet connectivity, non-availability of appropriate electronic devices, lack of a teaching environment at home, less information and communication technology (ICT) knowledge among students and teachers. It implied less engagement of students and teachers in the teaching and learning process.